TINJAUAN YURIDIS TERHADAP PUTUSAN HAKIM DALAM PERKARA TINDAK PIDANA KORUPSI (STUDI KASUS PERKARA NOMOR 21/PID.SUS- TPK/2015/PN.PBR DENGAN PERKARA NOMOR 26/PID.SUS- TPK/2015/PN.PBR) - Beauty. M, Conny; Indra, Mexsasai; ', Erdiansyah (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2016)
Corruption is an act done with the intent to provide an advantage that is not authorized by the rights of others wrongfully using his or her character to gain an advantage for himself or others. Impact of Corruption This may endanger the stability and security of societies, endanger the socio-economic development, and also political, as well as damage to democratic values and morality as slowly deeds is like to be a cultural as well as threats to the ideals of society towards a fair and prosperous. The purpose of this thesis, namely: First, to know the verdict against perpetrators of corruption in Case No. 21 / PID.SUS-TPK / 2015 / PN.PBR Case Number 26 / PID.SUS-TPK / 2015 / PN.PBR , Secondly, To know the basic legal consideration of judges in imposing criminal penalties against perpetrators of corruption in Case No. 21 / PID.SUS-TPK / 2015 / PN.PBR Case Number 26 / PID.SUS-TPK / 2015 / PN.PBR.This type of research used in the study of law is normative legal research, descriptive study, a study that aims to create a picture of the problems clearly and in detail. Source of data used secondary data consists of primary legal materials, secondary law, and tertiary legal materials. Data collection techniques in this study with a literature study method, after the data is collected and analyzed to be deduced. From the results of research and discussion can be concluded that, First, That the verdict against perpetrators of corruption in Case No. 21 / PID.SUS-TPK / 2015 / PN.PBR Case Number 26 / PID.SUS-TPK / 2015 / PN. PBR is still using the mindset of legal positivism and rarely found a judge who follows the way of thinking non-positivistic in deciding the case, wherein the case includes an extraordinary crime which negatively impact our nation and state, tend to interpret the law narrowly (textual) and still oriented judges are pragmatic. Thus, new construction mindset of judges based progressive law is needed judges in the process of deciding the corruption cases in order to become a judge idealistic as well as the realization of the purpose of law and the Law on Corruption. Second, Basic legal considerations of judges in imposing criminal penalties against perpetrators of corruption in Case No. 21 / PID.SUS-TPK / 2015 / PN.PBR Case Number 26 / PID.SUS-TPK / 2015 / PN.PBR by using juridical considerations, considerations of a non juridical and matters aggravating and mitigating matters criminal. In deciding against criminal judges tend to use more of juridical considerations than non juridical considerations.Keywords: Verdict Judge - Crime – Corruption